Integrity and Professionalism Driven Visionary Leadership of School Principals for Enhancing School Quality - Khaulah, Siti; Komariah, Aan; Kurniady, Dedy Achmad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the influence of visionary leadership based on integrity and professionalism on the quality of education in vocational high schools (SMK). The research method employed is quantitative, with data analysis techniques using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The sample consists of 246 vocational school teachers selected through cluster sampling in Bireun Regency, Aceh. The results indicate that visionary leadership based on integrity and professionalism has a significant impact on the quality of education in vocational schools. The school quality variable is explained by the visionary leadership construct, which comprises the dimensions of integrity and professionalism, accounting for 82.5% of the variance. The study finds that visionary leadership grounded in integrity and professionalism has a significant positive impact on educational quality in vocational high schools, explaining 82.5% of the variation in school quality. Professionalism-based leadership was identified as having the strongest influence on school quality, followed by integrity-based leadership and general visionary leadership, all of which proved statistically significant. The implications of these findings suggest that schools should emphasize strengthening integrity and professionalism in the leadership of school principals to sustainably improve educational quality. Enhancing visionary leadership will better equip schools to face educational challenges in the era of globalization and technological disruption. This research uniquely focuses on visionary leadership in vocational education, emphasizing integrity and professionalism as critical components, unlike previous studies that often addressed general school environments without these specific leadership dimensions.